Fostering Teacher Excellence: How Transformational Leadership Elevates School Performance - Hendriawan, Hendriawan; Ismail, Ismail; Bahrun, Bahrun (JURNAL AL-TANZIM, 2025)
This study aims to analyze the principal’s transformational leadership in improving teacher performance in schools. The research method employed is a qualitative approach, with data collection conducted through participant observation, in-depth interviews with the principal, vice principal for public relations, and teachers, as well as document analysis related to the principal’s transformational leadership. The study's results indicate that the principal employs transformational leadership, which fosters a positive work environment, encourages collaboration, and enhances teacher motivation. The individual attention given by the principal to teacher development is significant in improving their performance and creating a dynamic organizational culture. This culture motivates teachers to collaborate and improve the quality of teaching. Transformational leadership has a positive impact on teacher professionalism and performance, which ultimately improves educational outcomes. This study suggests that the application of the principal’s transformational leadership can enhance teacher performance and foster a positive organizational culture. These findings provide a reference for principals and related parties to strengthen leadership practices that support teacher professional development, thereby contributing to the improvement of education quality.